Sharing Session: Successful Student Entrepreneurshi Management at the University Level - Halim, Hendra; Hanidah, In In; Fadhil, Rahmat; Ramadhani, Evi; Rahimi, Sayyid Afdhal El; Khairi, Fitrah; Sari, Nurma; Muftahuddin, Muftahuddin; Amri, Khoirul; Raisa Ullya Nisva (Asian Journal of Community Services, 2024)
At the local level, student entrepreneurship management at Syiah Kuala University (USK) faces problems that align with these global challenges. This community service activity, a sharing session on student entrepreneurship management at Universitas Syiah Kuala, aimed to enhance the capacity of entrepreneurship program managers in integrating technology and innovation. Using the service learning method, participants were introduced to digital platforms and business management tools. The session involved collaborative efforts from various departments, focusing on improving the understanding and skills of the participants. Data collection included pre- and post-tests, showing a significant increase in participant competence. The results indicate that this approach is effective and can be replicated for broader applications, contributing to SDGs by promoting inclusive economic growth and supporting young entrepreneurs.